Pemahaman Tentang Ulu Al-Albab - Lutfiyah, Lujeng (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2017)
Reason is the most expensive and important property for human beings. It has a great influence on the black and white of the problem of the earth. It is the ability that makes humans burdened with obligations and assumes responsibility for choosing and willing. With the human mind can examine various things and events, and then take action decisions that affect the destruction or welfare of the earth. It is the decisive victory of a great struggle for power between the sacred duties of humanity vs. the animalistic lusts that have unstoppable armies of Satan. They are hard to resist due to their abstract shape, very smooth and can burst into every heartbeat even in every inch of human circulation. They can also come through various media that every day actively visits us without knowing the deadline.